Effect of industrial waste molecular sieves on internally cured cement-based materials - Shi, Peng; Li, Zhen; Chen, Xiaorun; Zeng, Lei; Hu, Rong (Frontiers in Materials, 2022)
Using waste molecular sieves (MS) instead of sand as water-absorbing fine aggregates in cement-based materials can effectively deal with factory adsorption waste and reduce sand consumption. In this article, the industrial waste molecular sieve is recycled and incorporated into cement-based materials. The effect of the molecular sieve as a hydration internal curing agent on the performance of cement-based materials is studied. A series of experiments are designed to find out the appropriate ratio and to evaluate and analyze the internal curing effect of waste molecular sieves. Compressive strength, flexural strength, and dry shrinkage properties of mortar with different dosages of the molecular sieve are tested. The water release behavior of the molecular sieve in mortar is comprehensively analyzed combined with the desorption test of the molecular sieve. Results show that the compressive and flexural strength increase by 5% and 10%, respectively, and the drying shrinkage decrease by 6% when 10% of sand is replaced by a molecular sieve under the same total water content. The hydration behavior of the sample is characterized by a microcosmic test of paste. Thermogravimetric analysis is used to calculate the content of corresponding hydration products and quantitatively describe the hydration degree of the internal curing paste mixed with MS. Results show that the content of hydration products is improved by the addition of the molecular sieve, which provides a theoretical basis for the enhancement of mortar to a certain extent.